1991
DOI: 10.1128/mcb.11.4.1988
|View full text |Cite
|
Sign up to set email alerts
|

Control of protein phosphatase 2A by simian virus 40 small-t antigen.

Abstract: Soluble, monomeric simian virus 40 (SV40) small-t antigen (small-t) was purified from bacteria and assayed for its ability to form complexes with protein phosphatase 2A (PP2A) and to modify its catalytic activity.Different forms of purified PP2A, composed of combinations of regulatory subunits (A and B) with a common catalytic subunit (C), were used. The forms used included free A and C subunits and AC and ABC complexes. Small-t associated with both the free A subunit and the AC form of PP2A, resulting in a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
206
3
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(215 citation statements)
references
References 25 publications
5
206
3
1
Order By: Relevance
“…The SV40ER encodes for LT and ST antigens, which are known to inactivate tumor suppressors such as p53, pRb and PP2A (Yang et al, 1991;Ali and DeCaprio, 2001), and recent studies have identified a role for several oncogenes and tumor-suppressor genes in the regulation of stemness properties (Pardal et al, 2005). For example, downregulation of p53 has been associated with increased selfrenewal, and upregulation of stem cell markers, such as Nanog, ABCB1 and CD44 (Jerry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The SV40ER encodes for LT and ST antigens, which are known to inactivate tumor suppressors such as p53, pRb and PP2A (Yang et al, 1991;Ali and DeCaprio, 2001), and recent studies have identified a role for several oncogenes and tumor-suppressor genes in the regulation of stemness properties (Pardal et al, 2005). For example, downregulation of p53 has been associated with increased selfrenewal, and upregulation of stem cell markers, such as Nanog, ABCB1 and CD44 (Jerry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that ST perturbs cellular targets that participate in human tumor development (Shenk et al, 1976;Crawford et al, 1978;Choi et al, 1988). The ability of ST to transform human cells requires binding to the abundant serine-threonine protein phosphatase 2A (PP2A) (Yang et al, 1991;Sontag et al, 1993). PP2A is a heterotrimer composed of a conserved catalytic C subunit, a structural A subunit and a regulatory B subunit.…”
Section: Introductionmentioning
confidence: 99%
“…While the functions of small t are incompletely understood, in cells that have been subjected to SV40 infection, it is reported to enhance viral replication and polyploidy of the host cells (Whalen et al, 1999) to facilitate transformation of the infected cells by LT in limiting growth conditions (Bikel et al, 1987;Martin and Chou, 1975;Rubin et al, 1982) and to promote induction of cell cycle progression in non-dividing cells, (Porras et al, 1999). Known cellular targets for small t are hsc70 (Srinivasan et al, 1997) and protein phosphatase 2A (Pallas et al, 1990;Yang et al, 1991). Other reported functions of small t include transcriptional activation of promoters of AP-1 (Frost et al, 1994) cyclin A (Porras et al, 1999), and cyclin D1 (Watanabe et al, 1996), repression of c-fos promoters (Wang et al, 1994), and down-regulation of the cdk inhibitor p27 KIP1 (Porras et al, 1999).…”
Section: Discussionmentioning
confidence: 99%